Pengembangan Media Pembelajaran Berbasis Powtoon dalam Meningkatkan Kemampuan Representasi IPA di Tengah Pandemi Covid 19 - Syaiful Arif*; Amalia Muthoharoh (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
The Hubei Province of Wuhan, China, is the starting point for the transmission of the Covid-19 virus. Severe Acute Respiratory Syndrome Coronavirus-2 which causes the Covid-19 virus to spread globally to Indonesia. The World Health Organization says that the Covid-19 virus can spread quickly and its effects span all aspects. The impact and prevention efforts in Indonesia require that all activities from studying, working and worshiping be carried out at home. The government urges the public to do social distancing, which means no crowd of 5 people is allowed. The impact on education requires learning without face to face so that in responding to this the teacher is advised to use distance learning. Renewal of distance learning can take advantage of cyber systems. One of the uses of cyber systems is the powtoon media. Powtoon media can develop 21th century skills, namely the ability to represent and learn without time and space boundaries. This study aims to develop powtoon-based learning media in improving the ability of science representation. Stages of developing media 1) preliminary study, 2) development stages, and 3) product testing. Sampling using random sampling techniques and cluster random sampling. Data were collected by direct observation, questionnaires, and multiple choice ability tests (pre-test and post-test). Then the analysis technique uses validity, practicality, and effectiveness which are described descriptively qualitatively and quantitatively. Based on the results of the development of data processing the validity of the material and media, the average value was 88.00 and 91.00 while the practicality average value was 88.00 then the effectiveness in the experimental class was 61.38 while the control class was 48.20. Based on the results of this analysis, it can be seen that the powtoon media is feasible to be implemented, helps facilitate understanding and increases the representation ability of students